A variety of exact solutions for fractional (2+1)-dimensional Heisenberg ferromagnetic spin chain in the semiclassical limit - Akhtar, J.; Tariq, K. U.; Khater, M. M. A.; Houwe, A.; İnç, Mustafa (Soc Mexicana Fisica, 2021)
This paper investigates exact voyaging (2 + 1) dimensional Heisenberg ferromagnetic spin chain solutions with conformable fractional derivatives, an important family of nonlinear equations from Schrodinger (NLSE) for the construction of hyperbolic, trigonometric and complex function solutions. The detailed rational sine-cosine system and rational sinh-cosh system were used to locate dim, special and periodic wave solutions successfully. These finding suggest that the proposed approaches may be useful to investigate a range of solutions inside a repository of applied sciences and engineering, with success, quality, and trust. In addition, graphical representations and physical expresses of such solutions are represented by a set of the required values of the parameters involved. The methods are essentially adequate and can be extended to different dynamic models that create the nonlinear processes in today's research.
Keywords: Heisenberg ferromagnetic spin chain; conformable fraction derivative; extended rational trigonometric method; exact solutions